Different potato virus Y strains frequently co-localize in single epidermal leaf cells and in the aphid stylet. (12th March 2021) - Mondal, Shaonpius; Ghanim, Murad; Roberts, Alison; Gray, Stewart M.
Abstract : Single aphids can simultaneously or sequentially acquire and transmit multiple potato virus Y (PVY) strains. Multiple PVY strains are often found in the same field and occasionally within the same plant, but little is known about how PVY strains interact in plants or in aphid stylets. Immuno-staining and confocal microscopy were used to examine the spatial and temporal dynamics of PVY strain mixtures (PVY O and PVY NTN or PVY O and PVY N ) in epidermal leaf cells of 'Samsun NN' tobacco and 'Goldrush' potato. Virus binding and localization was also examined in aphid stylets following acquisition. Both strains systemically infected tobacco and co-localized in cells of all leaves examined; however, the relative amounts of each virus changed over time. Early in the tobacco infection, when mosaic symptoms were observed, PVY O dominated the infection although PVY NTN was detected in some cells. As the infection progressed and vein necrosis developed, PVY NTN was prevalent. Co-localization of PVY O and PVY N was also observed in epidermal cells of potato leaves with most cells infected with both viruses. Furthermore, two strains could be detected binding to the distal end of aphid stylets following virus acquisition from a plant infected with a strain mixture. These data are in contrast with the traditional belief of spatial separation of two closely related potyviruses and suggest apparent non-antagonistic interaction between PVY strains that could help explain the multitude of emerging recombinant PVY strains discovered in potato in recent years.